2020
DOI: 10.1063/5.0031718
|View full text |Cite
|
Sign up to set email alerts
|

Transmission properties of van der Waals materials for terahertz time-domain spectroscopy applications

Abstract: This work contains results from studying the electro-optical properties of bulk and few-layered Van der Waals materials including intercalated graphene, phosphorene, and tungsten disulfide thin films. Different production methods and substrates are considered. The objective of the research is to assess the relevance of application of these materials in terahertz (THz) time-domain spectroscopy (TDS). Therefore, the study is conducted in the visible, NIR (near-infrared) and THz frequency ranges as the most criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…To obtain homogeneous thin films of multilayered h-BN layers laid on each other, the redispersed solution was filtered through a microporous (with a pore size of 0.2 μm) polytetrafluoroethylene membrane. Such films were widely studied for different two-dimensional materials and it was shown that dispersions of graphene oxides and molybdenum disulfide yielded high-quality films [3][4][5][6][7]. The thin films obtained as a result of dispersion filtration were transported or deposited by the method described above [8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…To obtain homogeneous thin films of multilayered h-BN layers laid on each other, the redispersed solution was filtered through a microporous (with a pore size of 0.2 μm) polytetrafluoroethylene membrane. Such films were widely studied for different two-dimensional materials and it was shown that dispersions of graphene oxides and molybdenum disulfide yielded high-quality films [3][4][5][6][7]. The thin films obtained as a result of dispersion filtration were transported or deposited by the method described above [8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…High quality films have been successfully developed using other two-dimensional materials (for example from dispersions of graphene oxide and molybdenum disulfide [4][5][6]), but not previously for h-BN. The thin films produced from filtering of the dispersion was achieved in accordance with a previously described method [7,8], marking a facile and scaleable method towards large-scale integration of the two-dimensional material. The membrane holding the thin film was carefully transferred to the desired (PET) substrate, with the side with the filtered h-BN in contact with the substrate surface.…”
Section: Methodsmentioning
confidence: 99%
“…High quality films have been successfully developed using other two-dimensional materials (for example from dispersions of graphene oxide and molybdenum disulfide [23,39,40]), but not previously for h-BN. The thin films produced from filtering of the dispersion was achieved in accordance with a previously described method [22,25], marking a facile and scaleable method towards large-scale integration of the two-dimensional material. The membrane holding the thin film was carefully transferred to the desired (PET) substrate, with the side with the filtered h-BN in contact with the substrate surface.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Additionally, the average size of the exfoliated particles is significantly less than the original bulk crystal(s) [21,23]. Hence, to produce large area devices using ultrasonicated 2D materials, it is necessary to fabricate thin films of the individual exfoliated particles of similar size and shape, that are uniformly distributed [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%